Paraneoplastic neutrophilic leukocytosis syndrome in a cat with recurrent mammary carcinoma - Jark, Paulo C. [UNESP]; Raposo-Ferreira, Talita M. M. [UNESP]; Terra, Erika M. [UNESP]; Matiz, Oscar R. Sierra[UNESP]; Anai, Letícia A. [UNESP]; Fonseca-Alves, Carlos E. [UNESP]; Tinucci-Costa, Mirela [UNESP]; Laufer-Amorim, Renee [UNESP]; De Nardi, Andrigo B. [UNESP] (SAGE Publications, 2015)
Case summary A spayed 12-year-old female domestic shorthair cat presented with nodular lesions on the ventral-right thoracic wall after complete mastectomy 4 months previously. The prior diagnosis was tubulopapillary mammary carcinoma with axillary lymph node metastasis, and a recurrence was confirmed. A gradual and sequential increase in the total number of leukocytes with severe neutrophilia (95.632/µl) developed over the course of the illness, along with an increase in the size of the recurrent mass. The severe leukocytosis did not show any response to antibiotic therapy, and no evidence of infection was observed. Bone marrow cytology confirmed hypercellularity in the myeloid cell lineage. Based on these findings, paraneoplastic neutrophilic leukocytosis syndrome was suspected. An incisional biopsy of the recurrent mass was consistent with recurrent tubulopapillary mammary carcinoma. Malignant epithelial cells stained positive upon immunohistochemistry for granulocyte–macrophage colony-stimulating factor, cytokeratin and vimentin. After the final diagnosis of paraneoplastic neutrophilic leukocytosis syndrome, the cat was euthanized at the owner’s request. Relevance and novel information This is a novel case of paraneoplastic leukocytosis syndrome associated with mammary carcinoma in a cat. Although there are some reports describing paraneoplastic leukocytosis in cats, the relationship between this syndrome and feline mammary tumors has not been described.